2018
DOI: 10.1111/bju.14358
|View full text |Cite
|
Sign up to set email alerts
|

Is magnetic resonance imaging‐targeted biopsy a useful addition to systematic confirmatory biopsy in men on active surveillance for low‐risk prostate cancer? A systematic review and meta‐analysis

Abstract: A pre-biopsy MRI should be performed before confirmatory systematic TRUS-guided biopsies in men on AS, together with MRI-targeted biopsies when indicated. A combined approach maximises cancer detection, although other factors within multivariate risk prediction can be used to aid the decision to biopsy in these men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 42 publications
(55 reference statements)
4
45
1
1
Order By: Relevance
“…In contrast to patients with high‐risk lesions on first MRI, patients with moderate‐risk lesions who had reassuring confirmatory biopsies approached the rate of progression in patients with no visible lesions (12.5% vs 10%). The rate of upgrading at targeted confirmatory biopsy of visible lesions in the present study was lower than that reported elsewhere (23% vs 35%). However, with 4 years’ follow‐up, 37% of patients with visible lesions on first MRI required radical therapy.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast to patients with high‐risk lesions on first MRI, patients with moderate‐risk lesions who had reassuring confirmatory biopsies approached the rate of progression in patients with no visible lesions (12.5% vs 10%). The rate of upgrading at targeted confirmatory biopsy of visible lesions in the present study was lower than that reported elsewhere (23% vs 35%). However, with 4 years’ follow‐up, 37% of patients with visible lesions on first MRI required radical therapy.…”
Section: Discussioncontrasting
confidence: 93%
“…Regardless of the confirmatory biopsy findings in MRInegative patients, during 4 years of follow-up, MRI and PSA monitoring with selective re-biopsy identified 10% requiring radical therapy. This is similar to the rate of radical therapy required in MRI-negative patients in other studies [5]. Furthermore, after the confirmatory biopsy, only 23 of the remaining 84 MRI-negative patients needed to be subjected to a repeat biopsy to identify these 10% with upgrading.…”
Section: Discussionsupporting
confidence: 77%
“…Stamatakis et al [28] found that among a cohort of men who met the Johns Hopkins AS criteria at diagnosis and subsequently underwent mpMRI, the MRI suspicion score (defined as low, medium or high) was a significant predictor for finding significant disease (≤50% tumour in any core, GG ≥ 2) on confirmatory biopsy. Similarly, other groups have found MRI-suspicion scores from PI-RADS to be a significant predictor of upgrading to GG ≥ 2 on confirmatory [11,29], as well as follow-up biopsies [30].…”
Section: Discussionmentioning
confidence: 60%
“…Current guidelines recommend use of mpMRI for men considering AS for an accurate disease staging to better inform the initial decision of AS [9]. Previous studies have found that for men on AS, a positive mpMRI is more likely to be associated with upgrading to Grade Group (GG) ≥2 than a negative mpMRI [10,11], and that a mpMRI with a Prostate Imaging-Reporting and Data System (PI-RADS) score of > 3 has a positive predictive value of over 60% for the detection of GG ≥ 2 PCa [12]. On the contrary, initial results from a prospective, randomised, trial (ASIST; Active Surveillance Magnetic Resonance Imaging Study) demonstrated that addition of mpMRI to an AS regimen did not significantly improve the detection rate of GG ≥ 2 PCa over the standard TRUS biopsies alone [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, accurate risk stratification and AS-confirmation on follow-up is mainly associated with TB. Since 6% (55/85) upgrades were not detected by TB alone, SB should not yet be omitted [14,17,28]. We acknowledge that we did not analyze differences in SB approaches (12-core-TRUS-biopsy versus extended 24-core transperineal scheme).…”
Section: Discussionmentioning
confidence: 99%